Single-handed [videorecording (DVD)] : the complete collection - McCarthy, Colm, 1973-; Byrne, Anthony, 1975-; McDonnell, Owen, 1974-; McElhinney, Ian, 1948-; McCabe, Ruth (Acorn Media, 2018)
After being caught in an affair with a senior officer's wife, Sergeant Jack Driscoll leaves Dublin and takes charge of a rural part of Ireland.